PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY, DEBT TO EQUITY RATIO DAN UNEXPECTED EARNINGSTERHADAP EARNING RESPONSE COEFFICIENT - Susanti, Siswanty Rahma (Kompartemen : Jurnal Ilmiah Akuntansi, 2017)
The purpose of this study was to determine the positive effect of disclosure of Corporate Social Responsibility (CSR), Debt to Equity Ratio (DER), and Unexpected Earnings (EU) response to Earning Coefficient (ERC). The analytical tool used in this study is multiple regression method. Samples used as many as 20 consumer goods companies listed on the IDX in 2011-2014. Based on the results of the research found that simultaneously Corporate Social Responsibility (CSR), Debt to Equity Ratio (DER), and Unexpected Earnings (EU) affect the response Earning Coefficient (ERC). While partially Corporate Social Responsibility (CSR) is not significant positive effect on Earning Response Coefficient (ERC), Debt to Equity Ratio (DER) is not significant positive effect on Earning Response Coefficient (ERC) and Unexpected Earnings (EU) has positive effect sigifikanterhadap Earning response coefficient (ERC). Keywords: Disclosure of Corporate Social Responsibility (CSR), Debt to Equity Ratio, Earnings danUnexpected (EU)